2020
DOI: 10.1080/17461391.2020.1751306
|View full text |Cite
|
Sign up to set email alerts
|

Local fat content and muscle quality measured by a new electrical impedance myography device: correlations with ultrasound variables

Abstract: The present study investigated the relationship between local fat percentage (SKfat) and muscle quality (MQ) estimated by a new hand-held electrical impedance myography (hEIM) device or derived from ultrasound and strength assessments. The right anterior thigh of 90 healthy participants (mean±SD; age=22.9±2.9 years; 46 men: BMI=23.9 ± 2.4 kgm -2 ; 46 women: BMI=21.1 ± 1.9 kgm -2 ) was scanned by hEIM and ultrasound. Correlations between SKfat, local subcutaneous fat (SUBfat), and echo intensity (EIus) were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Their results may partly justify our medium correlation between BF% and MRI measurements, since Skulpt Chisel TM has been shown to be accurate for evaluating global BF% also by other authors [ 17 , 21 ]. At any rate, it should be taken into account that local BF% obtained with EIM seems to be mostly related to subcutaneous fat, as recently highlighted by Longo et al [ 14 ]. Furthermore, limits of this device have been underlined by Wells et al who found significant differences in BF% when comparing EIM data with seven-site skinfold and hydrostatic weighing BF% estimates ( p < 0.05) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results may partly justify our medium correlation between BF% and MRI measurements, since Skulpt Chisel TM has been shown to be accurate for evaluating global BF% also by other authors [ 17 , 21 ]. At any rate, it should be taken into account that local BF% obtained with EIM seems to be mostly related to subcutaneous fat, as recently highlighted by Longo et al [ 14 ]. Furthermore, limits of this device have been underlined by Wells et al who found significant differences in BF% when comparing EIM data with seven-site skinfold and hydrostatic weighing BF% estimates ( p < 0.05) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The device was connected to a smartphone with a dedicated app via Bluetooth ® technology. Data from triplicate measurements were averaged as a single entry in our analysis [ 14 , 16 ]. Data provided by the device for all patients included BF% (a measure of body fat percentage) and muscle quality, with the latter ranging from 0 (worst) to 100 (best).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrated that both the peak GH and IGF-1 SDS are independent predictors of SMA in children and adolescents of short stature. SMA is a comprehensive marker that determines both SMI and FMI, and the GH/IGF-1 axis may regulate muscle density through complex mechanisms ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…From Kapur et al (2018b) Data obtained from groups of ALS and wild type mice have demonstrated that EIM parameters (e.g., 50 kHz phase and central frequency, the latter being a reactance-based measure derived from multifrequency data) are associated with maximum force production using electrical stimulation of the posterior tibial nerve (Li et al, 2016). EIM measures have also been associated with indices of muscle quality (e.g., echo intensity from ultrasonography, strength normalized to muscle mass) in humans (Longo et al, 2020). The explained variances for these single EIM measures predicting contractile force and indices of muscle quality have ranged 36-77% and will improve as machine learning approaches develop predictive algorithms leveraging numerous EIM measures obtained across multiple frequencies.…”
Section: A B Cmentioning
confidence: 99%